PENTINGNYA PERAN STRATEGI SUMBER DAYA MANUSIA DALAM MEMPENGARUHI RETENSI AUDITOR DI INDONESIA - Rudi Candra (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to analyze the influence of strategic human resource management to employee retention in audit firm using perceived organization support as a mediator variable. The samples in this study is the employee who work as auditor in audit firms in Indonesia. Method of data collection is conducted using questionnaire which distributed by e-mail to audit firms. Sampling method used in this study is purposive sampling. The amount of respondent in this study was 109 questionnaires which distributed among 11 city in Indonesia. The results of this study show that recruitment, training, compensation, and perceived organization support are parcially have a positive affect employee retention. Performance appraisal parcially do not affect employee retention. Strategic human resource management have a significant positive affect to perceived organizational support. The relationship between strategic human resource management and employee retention is fully mediated by perceived organizational support.